Recommendations for implementing rice carbon credit projects in Viet Nam - 2024-2028 Interim Period until the legal and regulatory framework for the carbon market is established - Tran, Dai Nghia; Le, Tong Hai; Sharick, Amber; Vu, Hong Trang; Nguyen, Bao Tran; Nelson, Katherine M. (International Rice Research Institute, 2024)
The Ministry of Natural Resources and Environment (MONRE) together with Ministry of Finance (MoF) are in the process of developing a framework for Viet Nam’s carbon market that will then be piloted in 2026 and made operational in 20281. Rice cultivation has been prioritized by the Ministry of Agriculture and Rural Development (MARD) to pilot carbon credit activities in the agriculture sector due to high greenhouse gas emissions (GHGs) mitigation potential2 and in support for the implementation of the newly approved “Sustainable Development Project for One Million Hectares of Specialized, Low-Emission High-Quality Rice Farming in association with Green Growth in the Mekong Delta region by 2030”3. The International Rice Research Institute (IRRI) and the Institute of Policy and Strategy for Agriculture and Rural Development (IPSARD) in partnership with key Government ministries and other stakeholders has hosted three workshops to better understand what is needed in the lead up to 20284. This policy brief outlines key take-aways for decision-makers and suggests next steps for the various market actors to better prepare the agricultural sector for the pilot and operational phases of carbon credit market development vis a vis the development of an interim working procedure. It is important to highlight the consensus of stakeholders in identifying the current gaps and needs to be addressed in a timely manner on the way towards 2028 and beyond.